Indonesian Criminal Law Study on the Misuse of Visum Et Repertum Evidence as a Means for Committing the Crime of Extortion - Rohmat, Rohmat; Dyah Nugraheni, Prasasti (Universitas Negeri Semarang, 2019)
The problem in this paper is how the position of the Visum et Repertum evidence in the Indonesian Criminal Code study, the strength of the Visum et Repertum evidence and how the Indonesian criminal law study of the Visum et Repertum evidence is used as a tool to commit extortion crimes. This type of research uses normative analysis research. The research material used is secondary. So the method of data collection was carried out through literature studies, while data analysis was carried out qualitatively. Based on the results it can be said that the strength of the Visum et Repertum evidence is only as a complementary instrument in seeking the truth. Someone who deliberately uses a post mortem for illegal gain, then that person cannot be considered a victim but another actor related to the witness. Based on the analysis of criminal elements in the monistic school and elements of criminal responsibility in the dualistic school, the perpetrators of these crimes have fulfilled the Dolus element. The research can be concluded that Indonesian criminal law has not directly controlled it. It can be said that the strength of the Visum et Repertum evidence is only a complementary instrument in seeking the truth. Someone who deliberately uses a post mortem for illegal gain, then that person cannot be considered a victim but another actor related to the witness.